Relationship between nidamental gland length and mantle length in female ommastrephes bartramii (Le Suer, 1821) from the southwestern area of the Atlantic ocean - Maxim, Cornelia (Cercetări Marine - Recherches Marines, 2026)
The paper presents the results of the observation or. the maturation stage in the species Ommatrephes bartramii caught in January-April 1978, in the southwestern area of the Atlantic Ocean, on the high seas. The ratio of nidamental gland length to mantle length was determined by measurements, as well as the relationship between these parameters at different maturation stages. The maturation ratio (m) is a significant index for a more precise determination stage in female Ommagtrephes bartramii both in field and laboratory conditions.